Effects of Seasonal Thermal Stratification on Nitrogen Transformation and Diffusion at the Sediment-Water Interface in a Deep Canyon Artificial Reservoir of Wujiang River Basin - Yongmei Hou (MDPI AG, 2021)
Watershed-scale nitrogen pollution in aquatic systems has become a worldwide concern due to its continuous impact on water quality deterioration, while the knowledge of key influencing factors dominating nitrogen transportation and transformation at the sediment-water interface (SWI) remains limited, especially in impounded rivers with an artificial reservoir. Hence, for a better understanding of the effects of thermal stratification on nitrogen transformation, we investigated the nitrogen species and isotopes in the sediment of a deep reservoir in Southwest China. Our results confirmed a significant difference in nitrogen species and isotopic composition in sediment between those in the thermal stratification period and non-thermal stratification period and indicated that the sediment biogeochemical process and transportation were clearly linked to the variations in water temperature and dissolved oxygen dominated by the process of thermal stratification. Significant seasonal differences in NH4+-N and NO3−-N in pore water of the upper layer (0–19 cm) revealed that nitrification exhausted NH4+ in the non-stratified period (NSP), and a potential low mineralization rate appeared when compared with those in the stratified period (SP). Seasonal differences in nitrogen species and isotope fractionation of δ15N-PON (about 2.3‰ in SP) in the upper layer sediment indicated a higher anaerobic mineralization rate of organic matter in SP than that in NSP. The diffusion fluxes of NH4+-N at SWI were 9.48 and 15.66 mg·m−2·d−1 in NSP and SP, respectively, and annual NH4+-N diffusion accounted for 21.8% of total storage in the reservoir. This study demonstrated that the nitrogen cycling processes, especially nitrification, denitrification, and mineralization, have been largely altered along with the changes in dissolved oxygen and that the diffusion of nitrogen species varied with the presence of the oxygen. The results contribute to the future study of watershed nitrogen budget evaluation and suggest that the endogenous nitrogen released from the sediment-water interface should be emphasized when aiming to fulfil water management policies in deep reservoirs.